Literacy abilities and well-being in children: Findings from the application of EUREKA, the Italian adaptation of the RAVE-O Program - Daniela Traficante; Valentina Andolfi; Maryanne Wolf (Firenze University Press, 2017)
This study presents the programs RAVE-O (Reading, Automaticity, Vocabulary, Engagement-Orthography) by M. Wolf and its Italian adaptation EUREKA (EnthUsiasm, ResEarch, CApacity). They are aimed at improving literacy in children through activities promoting engagement in written language processing. Data from an experimental research on the application of EUREKA show that this training has positive effects not only on literacy, but also on child's well-being, in general and in school context.   Abilità di lettura e benessere nei bambini: primi risultati dell'applicazione di EUREKA, adattamento italiano del programma RAVE-O In questo lavoro viene illustrato il RAVE-O (Reading, Automaticity, Vocabulary, Engagement-Orthography) di M. Wolf, un programma finalizzato al potenziamento delle abilità di lettura e scrittura attraverso attività, da svolgersi in piccolo gruppo, che stimolano il coinvolgimento attivo dei bambini nell'apprendimento del linguaggio scritto. Viene poi presentato uno studio sperimentale sull'adattamento italiano EUREKA (EntUsiasmo, RicErca, CApacità) (Traficante, 2017), che mostra l'efficacia dell'intervento non solo sull'apprendimento del linguaggio scritto, ma anche sull'esperienza di benessere generale del bambino e, in particolare, nel contesto scolastico.